The RUPIAH EXCHANGE RATE DYNAMICS: EVIDENCE FROM TOURISM, MONETARY FACTORS, AND OIL PRICE VOLATILITY - Eva Annisa; Dedy Yuliawan (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the impact of foreign tourist arrivals (WIS), money supply (JUB), foreign exchange reserves (CADEV), and the Oil Volatility Index (OVX) on the Indonesian Rupiah exchange rate (IDR/USD) from January 2015 to December 2024 using the Autoregressive Distributed Lag (ARDL) approach. The results indicate the existence of a long-run cointegrating relationship among the variables. In the short run, an increase in foreign tourist arrivals tends to strengthen the Rupiah, while increases in money supply and OVX lead to Rupiah depreciation. Meanwhile, foreign exchange reserves play a significant role in stabilizing and strengthening the Rupiah. In the long run, only money supply and foreign exchange reserves have a statistically significant effect on the exchange rate, whereas the effects of foreign tourist arrivals and OVX are temporary. The Error Correction Term (ECT) coefficient of −0.314825 indicates that approximately 31.48% of short-run disequilibrium is corrected each month, implying that the adjustment toward long-run equilibrium takes about three months. The model explains 61.23% of the variation in exchange rate movements. These findings provide important policy implications for Bank Indonesia, Ministry of Tourism of the Republic of Indonesia, and financial market participants in maintaining exchange rate stability.